Bank Runs Detection In Indonesia With Market Discipline Moderating Variable - Ramadhani, Risky Amelia (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2018)
Bank Runs appearas the effect of mismaturity match for banking industries to keep their own liquidity. This condition causes and makes depositors withdraw their own money out of their banks massively. This has been a global cycling phenomenon, besides banking crisises, that needs to be noticed by banking industries. This research aims to detect and analyse the determinants of bank runs either from bank fundamental factors or macroeconomic fundamental factors in 2004-2016 by using panel data regression with Fixed Effect Method (FEM). This result shows that both bank fundamental factors which are CAR and ROA have significantly negative and positive effects to bank runs. Moreover, LNT as one of the the macroeconomic fundamental factors, also has a significantly negative effect too to bank runs. This is also strengthened by Market Discipline as its Moderating Variable.